Peningkatan Motivasi Belajar dengan Orientasi Model Inkuiri Terbimbing Berbasis Microlearning pada Peserta Didik Kelas VIII - Nurandini, Anggelia; Hidayati, Siti Nurul; Aulia, Ernita Vika (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This study focuses on assessing the improvement in learning motivation of class VIII students at a junior high school in Surabaya after applying a microlearning-based guided inquiry orientation model. The research also evaluates different aspects of motivation to measure overall learning motivation, aiming to offer recommendations for educators to enhance future teaching methods and boost student motivation.Method – This study employed a one-group pretest-posttest design, concentrating on the increase in learning motivation among junior high school students through the application of a microlearning-based guided inquiry model. The data was collected using a questionnaire consisting of 20 statements, focusing on various aspects of learning motivation.Findings – The study results indicated that implementing the guided inquiry model with a microlearning orientation successfully increased learning motivation, as evidenced by the N-Gain test, which showed an average score of 0.70 in the moderate category. However, the lowest improvement was observed in the self-confidence aspect. This was partly because students' self-confidence had already developed prior to the application of the guided inquiry model with a microlearning orientation. Additionally, the low results in self-confidence were attributed to the teacher-centered learning approach, which reduced students' engagement. A possible solution is to adopt student-centered learning methods that foster motivation. Research Implications – This research aids educators in analyzing students' learning motivation. The implementation of effective learning methods is reflected in improvements across all aspects of motivation, with moderate to high levels. The integration of a microlearning-based guided inquiry model positively impacts students' motivation, as demonstrated by their attitudes toward various motivational aspects.